2020
DOI: 10.21037/atm-20-7515
|View full text |Cite
|
Sign up to set email alerts
|

The use of a 3D-printed individualized navigation template to assist in the anatomical reconstruction surgery of the anterior cruciate ligament

Abstract: Background: To explore the location accuracy and early clinical outcomes of using a 3D-printed individualized navigation template to assist in the reconstruction of the anterior cruciate ligament (ACL).Methods: A single center randomized control study was conducted. Patients with ACL injury were treated with a conventional operation or an operation assisted by a 3D-printed individualized navigation template (the 3D group). The primary endpoint was the accuracy of the actual reconstruction compared with the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“… 2020 Liu D et al. [ 174 ] Ann Transl Med 43 A drill template for ACL rupture The 3D-printed template showed good location accuracy and reduced intraoperative positioning time compared to the traditional method for ACL reconstruction. 2020 Wu Q et al.…”
Section: Basic Types and Clinical Applications Of Orthopedic 3d Print...mentioning
confidence: 99%
See 1 more Smart Citation
“… 2020 Liu D et al. [ 174 ] Ann Transl Med 43 A drill template for ACL rupture The 3D-printed template showed good location accuracy and reduced intraoperative positioning time compared to the traditional method for ACL reconstruction. 2020 Wu Q et al.…”
Section: Basic Types and Clinical Applications Of Orthopedic 3d Print...mentioning
confidence: 99%
“…Liu et al. [ 174 ] used 3D printing personalized navigation templates to assist in anterior cruciate ligament (ACL) reconstruction and found that the 3D printing guides were more accurately positioned compared to the conventional procedure, with no difference to the preoperatively designed bone access location and reduced intraoperative Positioning time was reduced. In patients with chronic lateral ankle instability (CLAI), Wu et al.…”
Section: Basic Types and Clinical Applications Of Orthopedic 3d Print...mentioning
confidence: 99%
“…With the increasing complexity of the surgery and surgical decision-making, 3D printing technology has emerged as a new surgical modality with the potential and convenience to make a huge impact in the field of surgery. The main ones include: pre-operative planning; 3D implants; 3Dpatient-specific instrumentation (PSI), pre-operative planning allows surgeons to visualize relevant anatomical structures and helps to perform complex surgery, [ 9 ] 3D implants can be used for direct replacement of large defects after tumor resection and to aid reconstruction in limb-preserving surgery, [ 35 ] and intraoperative use of PSI can be used to a large extent for more accurate placement of internal fixations, especially in the presence of abnormal anatomy and deformities. Duren [ 8 ] et al used a prototype drill guide to perform patellar tunnel determination in MPFL reconstruction, which improved accuracy and reduced time compared to the conventional approach, and Liu [ 9 ] et al also verified the effectiveness of this technique by using 3D-printed individualized navigation template to perform ACL reconstruction, which is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, intraoperative acquiring standard lateral fluoroscopy is not easy and also concluded that aberration from true lateral of as little as 5° will significantly increase MPFL femoral tunnel malposition. [7,8] Duren [8] et al used prototype drill-guide for patellar tunnel determination, and Liu [9] et al found high localization accuracy and short time by using 3D-printed individualized navigation template for anterior cruciate ligament reconstruction. Kong [10] et al found that 3D printing technique assisted technique shortened operative time reduced blood loss and intraoperative fluoroscopy in the treatment of distal radius intra-articular fractures in patients with K-wire fixation compared to non-assisted technique and concluded that the 3D printing technique is safe and effective in the treatment of distal radius fractures.…”
Section: This Study Was Funded By the National Natural Science Founda...mentioning
confidence: 99%
“…The finding supports the use of 3D printing technology to improve the accuracy of tibial and femoral tunnel placement in ACL reconstruction. Recently, Liu and his colleagues did a randomized controlled trial to investigate the use of a 3D printed individualized navigation template in anatomic ACL reconstruction [33]. The study compared the accuracy of ACL reconstruction between a conventional operation and operation assisted by a 3D printed individualized navigation template in 43 patients.…”
Section: Preoperative Planning Using 3dmentioning
confidence: 99%